Pharmacogenomic insights into amlodipine response: the role of CACNA1D, CACNA1C, and TRIB3 variants in hypertensive patients - Wahby M. Babaresh; Zakiullah; Sohaib Ahmad Sohail; Alija Baig; Malik Faisal; Aiman Begum; Haseenullah Shah; Zia Ul Hassan; Kiran Ijaz; Syed Muhammad Mukarram Shah; Aftab Ullah (PLoS ONE, 2025)
Hypertension affects over 1.28 billion individuals worldwide, yet response variability to calcium channel blockers (CCBs) like amlodipine remains a challenge. While pharmacogenomic studies have implicated genetic polymorphisms in treatment outcomes, the combined effects of multiple variants remain unclear. This study investigates the influence of CACNA1D (rs3774426), CACNA1C (rs2239050, rs7311382), and TRIB3 (rs2295490) variants, individually and in combination, on the antihypertensive response to amlodipine. A total of 133 hypertensive patients from Khyber Pakhtunkhwa, Pakistan, receiving amlodipine monotherapy were genotyped using ARMS-PCR and Sanger sequencing. Blood pressure response was defined as post-treatment systolic blood pressure (SBP) ≤140 mmHg and diastolic blood pressure (DBP) ≤90 mmHg. Statistical analyses were adjusted for age, gender, BMI, dose, family history of HTN and dietary habits. The CACNA1D rs3774426 TT genotype was significantly associated with non-response in 35 patients, showing higher SBP than the CC genotype (n = 69). Conversely, the CACNA1C rs2239050 GG genotype (n = 67) was linked to improved SBP and DBP control compared to the CC genotype (n = 25). Combined genotype models (CACNA1D–CACNA1C and CACNA1D–CACNA1C–TRIB3) showed strong unadjusted associations but lost significance after adjustment. These findings highlight the role of CACNA1D rs3774426 in predicting amlodipine non-response and demonstrate the potential of genetic screening for optimizing antihypertensive therapy. Integrating pharmacogenomics into clinical practice could enhance personalized treatment strategies, improving outcomes in hypertensive patients.